Predicting the Specific Surface Area and Pressure Drop of Reticulated Ceramic Foams Used as Catalyst Support - Inayat, Amer; Freund, Hannsjoerg; Schwab, Andreas; Zeiser, Thomas; Schwieger, Wilhelm; Freund, Hannsjörg (Advanced Engineering Materials, 2011)
Open-cell ceramic foams are attractive candidates as catalyst support owing to their remarkable heat and mass transfer characteristics. The accurate knowledge of the specific surface area and the pressure drop is a prerequisite for the reliable design of reactors with solid foam structures as internals. In this contribution, we propose a new correlation for the prediction of the pressure drop in reticulated ceramic foams using their predicted specific surface area. The correlation is based on an ideal tetrakaidecahedron geometry, which is the preferred representative geometry for reticulated foams. The validity of the correlation is demonstrated by experimental data of reticulated ceramic foams of different pores per inch (PPI), porosity, and material from the present study as well as from the open literature.